Specific Synthesis of 1,5-Disubstituted-1,2,3-triazolines Catalyzed by Surface Modified Activated Carbon with MsOH - Marishetty Hemmaragala, Nanjundaswamy; Abrahamse, Heidi (Current Organic Synthesis, 2016)
Surface modified activated carbon with methanesulfonic acid (AC-MsOH) is found to catalyze [3+2] cycloaddition reactions between alkyl/aryl azides and nitroolefins which yielded regioselective 1,5-disubstituted-1,2,3-triazolines in high yields under mild conditions.
Keywords: Activated Carbon